2015
DOI: 10.1080/15384047.2015.1016658
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy overcomes glucocorticoid resistance in lymphoid malignant cells

Abstract: Glucocorticoid (GC) resistance remains a major obstacle to successful treatment of lymphoid malignancies. Till now, the precise mechanism of GC resistance remains unclear. In the present study, dexamethasone (Dex) inhibited cell proliferation, arrested cell cycle in G0/G1-phase, and induced apoptosis in Dex-sensitive acute lymphoblastic leukemia cells. However, Dex failed to cause cell death in Dex-resistant lymphoid malignant cells. Intriguingly, we found that autophagy was induced by Dex in resistant cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Several previous studies have shown that autophagy can trigger autophagic death pathway, which is the predominant cell death mechanism in response certain chemotherapy [27,28]. On the other hand, many studies have proved that autophagy can also protect cells from apoptosis and various stress to counteract cell death after chemotherapy [6,7,11,29]. Therefore, autophagy is considered as an important target in intervention and treatment of cancers [30], and autophagymodulating agents also have been identified as potential cancer therapeutic agents [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies have shown that autophagy can trigger autophagic death pathway, which is the predominant cell death mechanism in response certain chemotherapy [27,28]. On the other hand, many studies have proved that autophagy can also protect cells from apoptosis and various stress to counteract cell death after chemotherapy [6,7,11,29]. Therefore, autophagy is considered as an important target in intervention and treatment of cancers [30], and autophagymodulating agents also have been identified as potential cancer therapeutic agents [31].…”
Section: Discussionmentioning
confidence: 99%
“…suggested to serve as a pro-survival mechanism that facilitates cancer cells to resistance therapy-induced cell death [7]. To verify this consumption, we firstly analyzed cell viability in LNCaP cells or LNCaP/CP cells in the presence or absence of 3MA.…”
Section: Inhibition Of Autophagy Induces Apoptosis In Cisplatin-resismentioning
confidence: 99%
See 1 more Smart Citation
“…205,209 However, in leukemia patients, high doses of CQ are needed to inhibit autophagy, which limits their therapeutic efficacy. 205,209 However, in leukemia patients, high doses of CQ are needed to inhibit autophagy, which limits their therapeutic efficacy.…”
Section: Cq Effects On Cancer Stem Cellsmentioning
confidence: 99%
“…Chloroquine and other inhibitors of autophagy have cytotoxic effects on diverse leukemia-initiating cell types such as CD34-positive and glucocorticoid-resistant clones. 205,209 However, in leukemia patients, high doses of CQ are needed to inhibit autophagy, which limits their therapeutic efficacy. 210 One potential explanation comes from the observation that CQ may kill leukemia cells independently from the early steps of the autophagy pathway, and this CQ effect can be neutralized by leukemia cells in vivo through exocytosis.…”
Section: Cq Effects On Cancer Stem Cellsmentioning
confidence: 99%